Increased Autophagy Levels Mediate Cisplatin Resistance in Cisplatin-Resistant Cells While Also Rendering Them Vulnerable to Autophagy Induction. (12th November 2018) - Duan, Guihua; Song, Zhengji; Qi, Min; Bai, Xuan; Wang, Jingzhai; Zhang, Yu; Zou, Xiaoping; Guo, Qiang; Wan, Ping
Abstract : Autophagy plays an important role in tumor development because of its capacity to maintain energy homeostasis by recycling damaged intracellular proteins and organelles, and increased autophagy levels are reported to mediate drug resistance in many cancers. However, whether high autophagy levels negatively impact tumor cell growth is unknown. Herein, we found that cisplatin (ddp)-resistant cells were more sensitive to glutamine (Gln) deprivation than ddp-sensitive cells, and they showed significant G1 arrest and increased apoptosis rates under Gln-deficient conditions. Furthermore, ddp-resistant cells had a higher level of autophagy, which mediated ddp resistance. Further analysis indicated that Gln deficiency could trigger apoptosis by enhancing activation of the autophagy signaling pathway AMPK/ULK1 in ddp-resistant cells due to their high basal autophagy level. Interestingly, ddp-resistant cells were more sensitive to rapamycin, and rapamycin could efficiently suppress the growth of ddp-resistant cells in vivo . Taken together, our study demonstrated that ddp-resistant cells became vulnerable to Gln deprivation because of their increased level of autophagy, and for the first time, we showed that suppressing the growth of ddp-resistant cells via enhancing autophagy induction was possible with rapamycin treatment.